Dielectric liquid pumping flow in optimally operated micro heat pipes. (May 2017) - Chang, Fun Liang; Hung, Yew Mun
Highlights: We study the effects of dielectric liquid pumping flow in micro heat pipes. Effects of dielectric pump on the circulation effectiveness are analysed. Analysis for different configurations and lengths of dielectric pump is performed. Significant thermal performance enhancement exceeding 220% can be achieved. Abstract: Micro heat pipe is a micro-scale capillary-driven two-phase heat transfer device of which thermal performance is governed by the strength of evaporation and the circulation effectiveness of condensate from the condenser to the evaporator. By employing a mathematical model based on the conservation laws, this study demonstrates the application of dielectric pumping flow in enhancing the circulation effectiveness of condensate and hence the thermal performance of micro heat pipes. Through the application of a non-uniform electric field, the Maxwell pressure gradient is induced to drive the condensate flowing towards the evaporator. Two different dielectric pump configurations are compared and the micro heat pipe using planar electrodes is found performing better than that with the pin electrodes. The performance enhancement of different dielectric pump lengths where the total amount of electrical energy of the pump is conserved is analysed. The dielectric pump performs the best when it covers the entire length of micro heat pipe. Compared to the case without dielectric liquid pumping flow, significant enhancement in the heat transport capacity can be obtained where the maximum enhancement exceeds 220%. Even with a significant performance enhancement, the use of dielectric pump renders a sufficiently small solid wall temperature drop of a micro heat pipe, justifying the typical characteristic of a phase-change heat transfer device.